Physical parameters of stellar population in star formation regions of galaxies - Gusev, Alexander; Sakhibov, Firuz; Egorov, Oleg; Kostiuk, V. S.; Shimanovskaya, Eelena V. (Monthly notices of the Royal Astronomical Society, 2023)
We present the results of a study of young unresolved stellar groupings (clusters, OB associations, and their complexes) associated with H ii regions, based on the coupling of spectroscopic, photometric and H α spectrophotometric observations of star formation regions. Along with our own observations, we use a part of the spectroscopic and H α data from the literature and open data bases. The study is based on the catalogue of 1510 star formation regions with ages ∼10-20 Myr in 19 spiral galaxies, compiled by us earlier. We study the morphology of stellar groupings and their relation with the associated H α emission region. Extinctions, gas chemical abundances, and sizes of star formation regions are measured. Using numerical simple stellar population models computed for metallicities fixed from observations to intrinsic colours of the studied star formation regions, we estimated ages and masses of stellar population of 400 young stellar groupings. Different relations between observational and physical parameters of the young stellar population in star formation regions are discussed.